L’énonciation aphorisante dans l’article de presse : une syntaxe sous contrôle(s) - Grégoire LACAZE (E-REA)
A newspaper article belongs to a speech genre that is particularly suited for the quotations of other people’s words. When writing an article, a journalist very often quotes words that have been uttered by different sources, which is common practice in the press. By doing so, the journalist is supposed to link the quoted words to an original speaker for every occurrence of direct speech inserted in a newspaper article.Due to the choice of direct speech as a form of reported speech, the journalist, namely the reporter, can adapt the original speech sequence in some way or another so that it might easily be embedded within the body of the article or within the peritext.The current study focuses on “secondary aphorisms” (Maingueneau 2012, our translation) that are present in the headlines of newspaper articles. Each aphorism is usually detached from an original text and it contains some words borrowed from a speaker, who is generally identifiable.This article aims at showing that secondary aphorisms have a syntax that is largely determined by the specificities of journalistic discourse and that also has some limitations originated from the journalist’s choices and from various pragmatic and semantic constraints.